Designing a Control System for an Airplane Wing Flutter Employing Gas Actuators - A. R. Ansari; A. R. B. Novinzadeh (International Journal of Aerospace Engineering)
The wing flutter is a dynamic instability of a flight vehicle associated with the interaction of aerodynamic, elastic, and inertial forces (aeroelastics phenomena). In this study, just the primary control is investigated. Also, in order to control the two-dimensional wing flutter, the force jet and pulse width pulse frequency (PWPF) are suggested. The PWPF modulator has the advantage of almost linear operation, low jet gas consumption, flexibility in addressing various needs, and good accuracy in presence of oscillations. This scheme makes use of quasi-steady dynamic premises and incompressible flow, as well as the thin airfoil theory. It should be noted that, to justify the application of the aerodynamic theory, we have speculated that the thruster jet ejected through a nozzle with a diameter smaller than several millimeters has a supersonic regime (with Mach number of the order of M≈3.5). Consequently, the interference of the thruster jet in the boundary layer, flow, and circulation around the airfoil which are characterized by low speed would be negligible. The operation of the jet as a thruster is handled by the PWPF modulator, and the process output is fed back to the system via a PD controller. In order to control the wing flutter oscillation, the location of installing the actuator on the airfoil is investigated.